2015
DOI: 10.4238/2015.march.20.19
|View full text |Cite
|
Sign up to set email alerts
|

A Cu/Zn superoxide dismutase from Jatropha curcas enhances salt tolerance of Arabidopsis thaliana

Abstract: ABSTRACT. Superoxide dismutases (SODs) are involved in protecting plants against diverse biotic and abiotic stresses. In the present study, a novel Cu/Zn-SOD gene (JcCu/Zn-SOD) was cloned from Jatropha curcas L. Quantitative reverse transcription-polymerase chain reaction analysis revealed that JcCu/Zn-SOD is constitutively expressed in different tissues of J. curcas and induced under NaCl treatment. To characterize the function of this gene with respect to salt tolerance, the construct p35S:JcCu/Zn-SOD was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Plants tend to produce massive reactive oxygen species under stress, inducing a destructive impact on the growth and physiological processes of plants. Besides the nonenzymatic antioxidant system, enzymatic antioxidants such as SOD, CAT and POD can also scavenge the reactive oxygen (Xia et al, 2020;Liu et al, 2014;Liu et al, 2015). The antioxidant enzyme activities of 'Hayward' and 'Hongyang' fruits in our study were similar to those reported in previous work (Yang et al, 2015;Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Plants tend to produce massive reactive oxygen species under stress, inducing a destructive impact on the growth and physiological processes of plants. Besides the nonenzymatic antioxidant system, enzymatic antioxidants such as SOD, CAT and POD can also scavenge the reactive oxygen (Xia et al, 2020;Liu et al, 2014;Liu et al, 2015). The antioxidant enzyme activities of 'Hayward' and 'Hongyang' fruits in our study were similar to those reported in previous work (Yang et al, 2015;Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…tabacum showed that plants damage caused by drought stress has been mitigated to some extent [13]. In the present study, we found that CsCSD genes revealed remarkably expression change compared to CsFSD1 , CsFSD2 , and CsMSD1 under drought stress, this observation was similar to the expression of SOD gens in other plants [18, 20, 69], and indicated that CsCSD genes may play primary roles in drought-resistance in tea plant. In addition, under cold stress, the expression trends of most Cs SOD genes expect for CsFSD2 were up-regulated comparing with 0 h at different stages.…”
Section: Discussionsupporting
confidence: 79%
“…Fe-SOD occurs in chloroplasts, and also in peroxisomes and mitochondria [ 3 ]. A considerable number of SOD genes have been cloned from various monocots and dicots [ 4 6 ], and, since the first SOD gene cloned from maize [ 7 ], reports have indicated that SODs are important for stress tolerance [ 8 , 9 ]. Additionally, plants with SOD gene families that have been characterized at the genome-wide level include Arabidopsis thaliana [ 10 ], Dimocarpus longan [ 4 ], Sorghum bicolor [ 11 ], Populus trichocarpa [ 5 ], Musa acuminate [ 6 ], Gossypium raimondii and Gossypium arboretum [ 12 ], and the numbers of each of the three SOD-type genes vary among them.…”
Section: Introductionmentioning
confidence: 99%